Do buyer–seller personality similarities impact compulsive buying behaviour?. Issue 4 (26th May 2021) - Ali, Fayaz; Tauni, Muhammad Z.; Ali, Ayaz; Ahsan, Tanveer
Abstract: This study investigates the influence of buyer–seller personality similarities on compulsive buying behaviour in a dyadic setting. To provide insights into the gaps in previous research, we collected both buyer and corresponding seller data, and considered sellers' personalities. Specifically, using difference score analyses and variance‐based structural equation modelling, we analysed 1038 buyer–seller dyads in service encounters. Compared with the effects of individual buyers' personalities on compulsive buying, the combined personality results showed that buyer–seller agreeableness similarities increase the compulsive buying behaviour of agreeable buyers. On the other hand, buyer–seller similarities in openness and neuroticism reduce compulsive buying. A further analysis showed that buyer–seller interactions mediate the effect of their extraversion and openness similarities on compulsive buying, while buyers' shopping enjoyment mediates the effect of their extraversion and neuroticism similarities on compulsive buying. Overall, compulsive buyers have interpersonally different buying behaviours when their personalities match (differ) with their corresponding sellers'. Thus, marketers can match agreeable buyers with similar sellers to promote sales, while dissimilar sellers should be complemented with open‐minded and neurotic buyers, in particular, to reduce losses.